The amelioration of ovarian dysfunction by hesperidin in malathion-treated mice through the overexpression of PCNA and FSHR proteins - Mahnaz Zarein; Asghar Zarban; Hamed Shoorei; Mehdi Gharekhani; Mohammadmehdi Hassanzadeh-Taheri (Heliyon, 2023)
Objective: Malathion (MAL), a pesticide used for decades, is a highly toxic substance. Several studies have documented the negative effects of such agents on reproductive organ physiology, but the precise mechanism of action in the induction of ovarian dysfunction remains unclear. Therefore, the purpose of this research was to examine the effects of the antioxidant hesperidin (HES) on ovarian damage and toxicity caused by malathion. Materials and methods: In this experiment, forty adult female bulb/c mice weighing 27–30 g were categorized into four groups, namely hesperidin (20 mg/kg, i.p.), malathion (3 mg/kg, i.p.), malathion + hesperidin, and control groups. Following a period of 35 consecutive days of treatment, mice were euthanized, and their ovarian tissues were gathered for the purposes of histopathological analysis by H&E staining, immunohistochemical assessment via proliferating cell nuclear antigen (PCNA) and follicle-stimulating hormone receptor (FSHR) immunostaining, and biochemical evaluation via measuring the levels of malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), tumor necrosis factor-alpha (TNF-α), and interleukin-1 beta (IL-1β). In addition, serum samples were collected from the blood of mice to perform hormonal analyses, especially 17β-estradiol (E2), progesterone (P4), luteinizing hormone (LH), and follicle-stimulating hormone (FSH). Results: The results demonstrated that MAL exposure resulted in the development of abnormalities in the architecture and structure of ovaries. Also, the treatment of mice with MAL led to declined follicular counts at all three stages, namely, primary, secondary, and tertiary, reduced serum levels of sex hormones, decreased immunoreactivity of FSHR and PCNA, and diminished activity of CAT and SOD enzymes. In contrast, it caused an increase in MDA, IL-1β, and TNF-α, as well as the count of atretic follicles. Nonetheless, it was observed that HES exhibited the ability to ameliorate the deleterious impacts of malathion across all the aforementioned parameters. Conclusion: Treatment with HES via upregulating the protein expression of PCNA and FSHR and activating antioxidant defense was able to ameliorate the adverse effects of MAL on ovarian tissues.